Advances in aerospace guidance, navigation and control : selected papers of the fourth CEAS Specialist Conference on Guidance, Navigation and Control held in Warsaw, Poland, April 2017 /: selected papers of the fourth CEAS Specialist Conference on Guidance, Navigation and Control held in Warsaw, Poland, April 2017. ([2018]) - Unknown
No abstract available